Suitable stacking sequence of glass fibre reinforcements for specific application of composite using Taguchi design and finite element method. (14th September 2022) - Datta, Mallika; Nath, Devarun; Das, Srijan; Malitha, Mainul
The effect of stacking sequence of the various forms of glass fibre reinforcement on unsaturated polyester resin composite subjected to tensile and flexural loading was investigated. The Taguchi statistical technique had been used to identify a sustainable stacking sequence with unidirectional glass filament structure, glass fibre chopped strand mat, and woven glass roving mesh as reinforcement. The study used top, middle, and bottom layer positions of the reinforcing material stack inside the composite as control factors for tensile strength, and as well as flip (turning the face of the sample about the testing probe) for flexural strength. Response tables and analysis of variance were used to identify the most influential factors, and response graphs indicated the most important level for control factors. It was demonstrated that the location with the highest contribution for tensile strength was the middle layer, and in the instance of flexural loading, the bottom layer rear to the probe of the universal testing machine was the primary control factor. The strongest level was found to be one made of chopped strand mat sandwiched between two cross-oriented unidirectional filament structures. The uniqueness of this research is to establish the optimal way to stack reinforcements in superstructures such as walls, tables, beams that are only partially supported, poles, and boats, considering the different types of loads and the directions in which the forces act. The Finite Element Method (FEM) was used, to simulate the findings.